Agroecological functions of the agrobiodiversity niches of rural Bogota, Colombia - Stefan Ortiz; Catalina Quiroga-Manrique; Julieth Monroy-Hernández; Darío Pérez (Íconos)
The rapid expansion of industrial agriculture in rural Bogotá has led to a reduction in the diversity of plants cultivated by peasant families. This generates transformations in livelihoods and biocultural relations, affecting local environmental knowledge and practices for the use and management of agrobiodiversity. Although several studies have documented the presence of agrobiodiversity niches, such as orchards and peasant gardens that persist amid homogenized landscapes, there is a need to expand the identification and analysis of the multiple cultural and agroecological functions that characterize them. This study aims to identify local environmental knowledge linked to orchards and gardens in terms of their functions and contributions to the conservation and recovery of agrobiodiversity. For this purpose, semi-structured interviews were conducted with six key local informants and twenty-five peasant households, including ethnographic observations and ethnobotanical walks. Based on the information obtained, the agrobiodiversity niches were characterized in terms of their functionality according to the daily experiences of their caretakers. Eight agroecological functions, 249 common names associated with the same number of plant species, and knowledge about uses and management were identified. Finally, the possible articulations of the niches with the surrounding landscapes and water spaces were analyzed to understand their potential contribution to territorial transformations and to the connectivity of the rural ecological structure of Bogota.